Electric-field and strain effect on magnetism on transition metal dichalcogenides - Gonchigsuren, Munkhsaikhan; Dorj, Odkhuu (Journal of Applied Science and Engineering A, 2021)
Herein, from first-principles density functional calculations, intrinsic magnetism and magnetocrystalline anisotropy (MA) in two-dimensional (2D) structure and individual atom pairs are shown effectively controllable by means of simultaneous voltage and strain effects. By tuning the strain in transition metal dichalcogenides (TMDs) MoS2, WS2, MoSe2 and WSe2 with Os adatom as a model system, we demonstrate that the voltage dependence of MA varies from an extremely large value of 150 meV/Os in perpendicular to the lateral plane into -25 meV/Os in plane by an electric field of only 0.1–0.2 V/Å.